Analisa Kinerja Sistem Air Bersih di Desa Ponelo Kecamatan Ponelo Kepulauan - Nurain Naha; Aryati Alitu; Apriyanto A. Pahrun (Research Review: Jurnal Ilmiah Multidisiplin, 2025)
This research employs a quantitative approach, which includes assessing community satisfaction with clean water services and testing water quality based on the standards outlined in the Minister of Health Regulation No. 2 of 2023. The results indicate that community perception falls into the "Strong" category at 79.22% regarding water availability during the dry season, but only 55.32% of respondents expressed satisfaction with the clean water program, indicating a relatively low level of satisfaction. It can be concluded that the dry season has a significant impact on the availability and quality of clean water. The quality test results indicate that the water used by the community does not meet the clean water standards set by the Ministry of Health. Several physical and microbiological parameters, such as turbidity and the presence of E. coli and Coliform exceed the permissible limits for potable water. This research recommends that the governmenwor related agencies pay greater attention to clean water treatment in order to maintain water quality.